Friday

April 18, 2014

April 18, 2014

Posted by **Loren** on Sunday, September 11, 2011 at 11:27pm.

3x - 5y = 11

x - 3y = 1

- Algebra 1 -
**Anonymous**, Monday, September 12, 2011 at 2:59amEquation 2 looks like it would be easy to solve for x, so we take it and isolate x:

x - 3y = 1

x = 1 + 3 y

Now we can use this result and substitute x = 1 + 3 y in for x in equation 1:

3x - 5y = 11

3 * ( 1 + 3 y ) - 5 y = 11

3 + 9 y - 5 y = 11

3 + 4 y = 11

4 y = 11 - 3

4 y = 8 Divide both sides with 4

y = 2

x = 1 + 3 y

x = 1 + 3 * 2

x = 1 + 6

x = 7

**Related Questions**

algebra - I have to solve this equation using substitution. 3x+5y=10 2x+ 1/2y=24...

Algebra - solve using substitution method 3x-5y=61 3x-y=17

algebra 1 - Solve the Foll by substitution x=1/5y 3x+2y=26 So, substitute 1/5y ...

algebra 1 - how do you solve the following questions using the substitution ...

Algebra 1 - What is an equation of a line perpendicular to the line with ...

algebra - how do i solve this equation by using substitution? 2x+y=4 3x+2y=1 ...

substitution - solve by the substitution method 3x+5y=21 x=51-9y

substitution - solve by the substitution method 3x+5y=21 x=51-9y

algebra - -3x-5y=-6 6x+5y=-34 how do i solve this using elimination?

Algebra 1 - explain: 3x-y=12 4x-5y=16 it is linear equations using substitution ...